Irregularity molecular descriptors of VC5C7[m,n] and HC5C7[m,n] nanotubes - Munir, Muhammad Mobeen (Frontiers in Physics, 2022)
Scientific organizations are creating carbon nanotube-based composites like VC5C7[m,n] and HC5C7[m,n], which indicate significant response against voltage. Imbalance-based irregularity indices determine the degree of irregularity of a certain molecular structure and, as a result, determine the properties of a molecular substance. In this article, we aim to compute irregularity indices of two nanotubes, VC5C7[m,n] and HC5C7[m,n]. We produce formulas for the irregularity of these two nanotubes, which are functions depending on the parameters of the structure m and n. We compare our results graphically and conclude that VC5C7[m,n] is more irregular than HC5C7[m,n].